Jurisdiction and Locus Delicti of Transnational Cybercrime: a Normative Study Of International Law and Indonesian Telematics Law - Agustinus Nicholas L Tobing; Annisa Fitria (Interdisciplinary Social Studies, 2025)
This study examines the determination of jurisdiction and locus delicti in transnational cybercrime from the perspective of international law and Indonesian telematics law. The borderless nature of cyberspace poses complex challenges for identifying the crime scene (TKP) and enforcing jurisdiction, as perpetrators may operate from one country while causing impacts across multiple states. Using a normative juridical method, the research analyzes primary legal materials such as the Budapest Convention on Cybercrime, the United Nations Convention against Cybercrime (2024), Indonesia’s Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law), Law No. 27 of 2022 on Personal Data Protection (PDP Law), and the Draft Law on Cybersecurity and Resilience (RUU KKS). Case studies—including cyberattacks on Taiwan (2024–2025), INTERPOL’s 2025 Africa ransomware report, and the 2025 transnational financial crime operation—demonstrate how concurrent and extraterritorial jurisdiction principles apply in practice. The findings indicate that the locus delicti in cybercrime is multifaceted, encompassing the perpetrator’s location, the breached server, and the place where damage occurs. Effective prosecution requires coordination through international cooperation and harmonization of national regulations with global conventions. The study concludes that Indonesia must strengthen its legal framework by ratifying the UN Convention against Cybercrime, adopting concurrent jurisdiction principles, and establishing an inter-agency task force for cross-border investigations to enhance legal certainty and protect national interests in the digital era.